2019
DOI: 10.1080/03009742.2019.1611918
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of osteoporotic fractures in Swedish patients with rheumatoid arthritis despite early treatment with potent disease-modifying anti-rheumatic drugs: a prospective general population-matched cohort study

Abstract: Survival analysis (Kaplan-Meier method), comparison between the total population of RA patients compared to matched controls over the entire follow-up time. Figure A. show the cumulative survival of forearm fractures between RA patients and controls. B. show the cumulative survival of upper arm fractures between RA patients and controls. C. show the cumulative survival of hip fractures between RA patients and controls. D. show the cumulative survival of other fractures between RA patients and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A Swedish study found an increased risk of fragility fractures in RA in both the 1990s and 2000s, despite patients in the 2000s receiving potent pharmacological treatment early in the disease. This study, however, was not focused on vertebral fractures, but on other fragility fractures such as upper arm, hip and other fractures [22]. Similarly, an upward trend in the incidence of hip fracture in Spanish RA patients between 1999 and 2015 was reported, despite a decreasing age-adjusted incidence in the Spanish general population [24,25].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A Swedish study found an increased risk of fragility fractures in RA in both the 1990s and 2000s, despite patients in the 2000s receiving potent pharmacological treatment early in the disease. This study, however, was not focused on vertebral fractures, but on other fragility fractures such as upper arm, hip and other fractures [22]. Similarly, an upward trend in the incidence of hip fracture in Spanish RA patients between 1999 and 2015 was reported, despite a decreasing age-adjusted incidence in the Spanish general population [24,25].…”
Section: Discussionmentioning
confidence: 92%
“…However, not all authors have found this beneficial effect [10]. Recent data referring to the prevalence of fractures are scarce, particularly those referring to vertebral fractures, as most series are focused on non-vertebral fractures [21][22][23]. Notably, Ozen et al in 2019 showed a reduction in the risk of vertebral fracture in RA patients treated with anti-TNFα [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the US, data show that osteoporotic fractures account for about one-third of RA-related mortality 5 . Fractures increase morbidity and mortality, reduce quality of life, reduce independent functioning of people, especially in old age, and increase economic burden 6 , 17 . Vertebral fracture is one of the most common fractures due to decreased BMD, which causes limitation of activity, disability, kyphosis and decreased pulmonary function 10 , 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Bone loss starts already early in the disease course [ 4 ] and increases with longer disease duration [ 5 ]. The prevalence of bone loss and the risk of osteoporosis-related fragility fractures (both vertebral and non-vertebral) is about double that expected in non-RA populations [ 6 8 ]. Despite recent therapeutic advances, the risk of fragility fractures in RA is still increased compared with that in the general population [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%